"n Kritiese evaluasie van die Godsbeeld van Sally McFague - Steyn, L. (Hervormde teologiese studies, 1993)
Sally McFague’s image of God: A critical evaluation In the past decade, many feminist publications on the image of God have seen the light of day. This article concentrates on the viewpoint of Sally McFague in addressing the problem of God-language. It attempts to poin t ou t the positive and negative aspects of McFague’s images of God-as-Mother, God-as-Lover and God-as-Friend. Finally, it aims to pinpoint the value of the feminist viewpoint for theological discussion in general and the proclamation of the church today in particular.